Screening and Quantification of Marine Actinomycetes Producing Industrial Enzymes Amylase, Cellulase and Lipase from South Coast of India - Selvam, K (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Fifty six actinomycete strains were isolated from marine sediments of south Indian coastal region of India. The isolates were identified as actinomycete by morphological studies. Among these, nine isolates were selected on the basis of their amylolytic, cellulolytic, lipolytic activities by screening. Amylolytic and cellulolytic activities were exhibited by the strains 1, 3, 51 and 12, 29, 49 and it was confirmed by formation of clear zones of hydrolysis around the colonies. Lipolytic activity was exhibited by the strains 3, 10, 28 and it was indicated by formation of orange fluorescent halo around the colonies. Among the isolates maximum amylase, cellulase and lipase activities were exhibited by strains 3, 49 and 28 and it was determined by DNS (3, 5-dinitrosalicylic acid) assay method and titrimetric assay method. The enzyme activity of the strains 3, 49 and 28 was found to be 6.48, 8.93, and 700U/ml.